(untitled) (Research, Society and Development, 2021)
The leek (Allium porrum L.) belongs to the Aliáceae family, a group of great economic importance, besides the species there are also onion, chives and other garlic varieties. There´s not so much knowledge about its growth and development, however, it is known that the vegetative development of a plant varies depending on the intrinsic characteristics of each species or cultivar, the weather conditions of each crop and the cultivation environment, as well as the practices agricultural adopted. Considered that, the objective of the work was to determine if the affected spacing between plants and lines in relation to the vegetative and productive characteristics of leeks. The design used was a randomized block with four replications, distributed in: 0.50 x 0.25 m; 0.50 x 0.20 m; 0.50 x 0.15 m; 0.50 x 0.10 m; 0.40 x 0.15 m; 0.40 x 0.10 m; 0.30 x 0.20 m and 0.30 x 0.15 m. Assessments were carried out when the plants reached their maximum vegetative development: plant height (cm), pseudostem height (cm), pseudostem diameter (mm), fresh shoot weight (g), number of leaves, leaf area (cm2), dry leaf weight (g), pseudostem dry weight (g) and productivity. The spacing did not interfere with the variables of plant height, number of leaves, and leaf area, however, the productivity variables of the leek culture were influenced by the spacing between plants and lines. Thus, based on the results obtained, it is recommended to use the 0.50 x 0.10 m and 0.30 x 0.15 m spacings, due to the increased productivity for the leek culture.